A psicologia e as políticas públicas de saúde: um estudo sobre a atuação da(o) psicóloga(o) na atenção primária à saúde no município de Fortaleza - Silva, Emylio César Santos da (2012)
The international recognition of the Primary Health Care (PHS) as the foundation for a new model of health care has led to changes in theory and practice of various professions of health and welfare, among them psychology. In Brazil, the PHS was established as the main entrance of the user services the Unified Health System (SUS) was developed by Family Health Strategy (FHS). Despite the remarkable expansion of the role of psychologists in the PHC in the municipalities of all Brazilian regions, there are few studies that have attempted to address the issue on the training and professional in this context. This study discusses the role of psychologists in the PHC in Fortaleza, to support the Family Health Teams (FHT). The finding that health services, specifically the Centers for Family Health (CFH) constitute recent local work of psychologists and that these practices are characterized as different forms of performance compared to other contexts justifies the relevance of this study. This is an exploratory study of qualitative nature. Investigated demographics, training and performance in the context of public health policies. The survey was conducted in health facilities with 10 psychologists with at least one year of work in the APS. For data collection we used a semi-structured interviews. Data processing used the content analysis of Bardin. We found that psychologists who work in this context are facing difficulties related to the performance of team activities that are presented by factors ranging from deficient training in an interdisciplinary within a multiprofessional context up to difficulties because they are packed in units of health range from two to four, making it difficult and reduces the ability to link between health teams and territories of coverage of Family Health Teams and the Family Health Support Teams (FHST).